2016
DOI: 10.1073/pnas.1515129113
|View full text |Cite
|
Sign up to set email alerts
|

Infants ask for help when they know they don’t know

Abstract: Uncertainty monitoring is a core property of metacognition, allowing individuals to adapt their decision-making strategies depending on the state of their knowledge. Although it has been argued that other animals share these metacognitive abilities, only humans seem to possess the ability to explicitly communicate their own uncertainty to others. It remains unknown whether this capacity is present early in development, or whether it emerges later with the ability to verbally report one’s own mental states. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
134
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 197 publications
(142 citation statements)
references
References 36 publications
(60 reference statements)
7
134
0
1
Order By: Relevance
“…These findings build on the findings of Goupil et al (28) by showing that deliberate teaching and reinforcement are not required for the production of gestures signaling ignorance. Many children produce such a signal in the course of everyday interaction outside the laboratory.…”
Section: Signaling Ignorancesupporting
confidence: 85%
See 1 more Smart Citation
“…These findings build on the findings of Goupil et al (28) by showing that deliberate teaching and reinforcement are not required for the production of gestures signaling ignorance. Many children produce such a signal in the course of everyday interaction outside the laboratory.…”
Section: Signaling Ignorancesupporting
confidence: 85%
“…However, recent evidence indicates that human infants are capable of signaling their ignorance. Goupil et al (28) trained 20-mo-old infants to ask their caregiver for guidance if they were uncertain of a hidden object's location. More specifically, infants watched as a toy was hidden in one of two opaque containers.…”
Section: Signaling Ignorancementioning
confidence: 99%
“…Yet verbally reporting one’s own mental states involves more than pure metacognitive monitoring [34, 35]. Consistent with this idea, metacognition has been found to involve both explicit and implicit processing modes in adults [15, 34, 35, 36], and a few recent studies found that children can pass metacognitive tasks at younger ages when no verbal report is required [31, 33, 37]. In particular, we found that 20-month-old infants are able to ask for help non-verbally in order to avoid making errors [37].…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, after 1-½-year-old infants pointed to one of two boxes in order to obtain a hidden toy, they waited longer for an upcoming reward (such as a toy) when their initial choice was correct than when it was wrong, suggesting that they monitored the likelihood that their decision was right (57,65). Moreover, when given the opportunity to ask (nonverbally) their parents for help they chose this opt-out option specifically in trials in which they were likely to be wrong, revealing a prospective estimate of their own uncertainty (66). That infants can communicate their own uncertainty to other agents further suggests that they consciously experience metacognitive information.…”
Section: Foundations Of C2 Consciousness In Infantsmentioning
confidence: 99%